Images as tools of social control: an analysis of the production of identities in contemporary mass-culture - Garner Bafa, James (Michaelis School of Fine Art, 2023)
The multi-media paintings and works on paper which form the basis of my work are in essence an attempt to subvert the production of identities in contemporary mass-culture. In employing the term "mass-culture" I wish to refer to a network of interlinked forms which dominate contemporary existence. The mass-media are commonly cited as the major players with respect to mass-culture, entrenching commodity-fetishism and systems of stereotypes which play a vital role in determining social norms. These "stereotypes" are continually being adapted in order to facilitate the illusion of being new, relevant and fashionable. At the same time this process encourages an insatiable appetite for new images and fashions, to the extent that culture and fashion converge. Despite the fact that these mass-cultural stereotypes appear to be in a constant state of flux, it is important to realise that the vast majority of these changes are changes in appearance alone. The mind-sets behind the masks remain largely unchanged, as too do the aspirations and fears these images embody.